Intertextualité et forme dans le roman caribéen-canadien : de l’écriture dystopique de Neil Bissoondath au roman polysystémique de Ramabai Espinet - Rodolphe Solbiac (Revue LISA)
This study investigates the modes of intertextuality at play in the writing of Ramabai Espinet’s novel The Swinging Bridge. It proposes to approach the intertextuality between this work and A Casual Brutality and The Worlds Within Her as refunctioning of the issues dealt with by Neil Bissoondath. It argues that Espinet reworks texts of the history of Trinidad and Tobago as well as Bissoondath’s fiction texts. It demonstrates that The Swinging Bridge constitutes a literary polysystem that responds to Bissoondath’s dystopian fiction and reconstruction of history which promotes cultural hybridity and diasporic belongings as alternatives to cultural conflict and dislocation.